2001
DOI: 10.1159/000057011
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic breakpoint within RAD51L1 in a t(6;14)(p21.3;q24) of a pulmonary chondroid hamartoma

Abstract: Rearrangements involving chromosome region 14q23→q24 represent a main cytogenetic subgroup in a variety of benign solid tumors. Recently, in uterine leiomyomas containing the classical t(12;14)(q15;q23→q24), the primary chromosome 14 target gene was identified as the protein kinase-encoding gene RAD51L1. In this report we show that RAD51L1 is also involved in the frequently ocurring t(6;14) (p21;q23→q24) in pulmonary chondroid hamartomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Compulsive buying is prevalent in areas in which the consumer culture predominates (Black, 2001). Psychological variables believed to operate in compulsive buying in Western research were conceptualized into two separate pathways and validated here with a Chinese college sample.…”
Section: Discussionmentioning
confidence: 99%
“…Compulsive buying is prevalent in areas in which the consumer culture predominates (Black, 2001). Psychological variables believed to operate in compulsive buying in Western research were conceptualized into two separate pathways and validated here with a Chinese college sample.…”
Section: Discussionmentioning
confidence: 99%
“…In pseudo-Meigs' syndrome, which is characterized by uterine leiomyomas, ascites, and pleural effusion, a combination of the HMGA2/RAD51L1 fusion and a loss of the second RAD51L1 allele were observed (29). In addition, RAD51B is involved in other types of balanced chromosome translocations in pulmonary chondroid hamartomas (30) and thymomas (31). These studies indicate that at least one allele of RAD51B is altered in some benign tumors, but the key pathologic event is still unclear.…”
Section: Introductionmentioning
confidence: 95%
“…Interesting, HMGA2 was recently proved to be directly involved in DSBR pathway (30,31). RAD51L1 is also involved in the frequently occurring t (6;14) (p21;q23/q24) in pulmonary chondroid hamartomas (32). In addition, a recent genome-wide association study identified RAD51L1 as a new susceptibility gene for breast cancer risk (33).…”
Section: Discussionmentioning
confidence: 99%